2003
DOI: 10.1084/jem.20030891
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Adenine Nucleotide Phosphohydrolysis and Nucleoside Signaling in Posthypoxic Endothelium

Abstract: Limited oxygen delivery to tissues (hypoxia) is common in a variety of disease states. A number of parallels exist between hypoxia and acute inflammation, including the observation that both influence vascular permeability. As such, we compared the functional influence of activated polymorphonuclear leukocytes (PMN) on normoxic and posthypoxic endothelial cells. Initial studies indicated that activated PMN preferentially promote endothelial barrier function in posthypoxic endothelial cells ( Ͼ 60% increase ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
596
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 451 publications
(640 citation statements)
references
References 48 publications
33
596
2
4
Order By: Relevance
“…The transcription factor hypoxia inducible factor (HIF) is also overexpressed in renal hypoxia and is in part responsible for the increased expression of A 2B R in this setting [54]. Another transcription factor, cAMP receptor binding protein (CREB), also increases A 2B R expression [55,56]. As discussed above, the A 2B R is a G s -coupled protein receptor, which activates adenylyl cyclase and increases cAMP production; thus, this serves as a positive feedback mechanism wherein A 2B R increases its own expression and promotes renal fibrosis in the setting of hypoxia.…”
Section: Unique Aspects Of Adenosine Receptor Signaling In Organ Fibrmentioning
confidence: 99%
“…The transcription factor hypoxia inducible factor (HIF) is also overexpressed in renal hypoxia and is in part responsible for the increased expression of A 2B R in this setting [54]. Another transcription factor, cAMP receptor binding protein (CREB), also increases A 2B R expression [55,56]. As discussed above, the A 2B R is a G s -coupled protein receptor, which activates adenylyl cyclase and increases cAMP production; thus, this serves as a positive feedback mechanism wherein A 2B R increases its own expression and promotes renal fibrosis in the setting of hypoxia.…”
Section: Unique Aspects Of Adenosine Receptor Signaling In Organ Fibrmentioning
confidence: 99%
“…A number of studies have revealed that HIF elicits a barrier protective program in the intestine [17][18][19][20]. While originally guided by microarray analysis of differentially expressed messenger ribonucleic acid (mRNA) in cultured epithelial cells subjected to hypoxia, these studies have proven robust in a number of animal models of inflammation.…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 99%
“…Third, HIF-dependent epithelial barrier-protective pathways driven by hypoxia tend to be more "nonclassical" regulators of barrier function. Rather than classic junctional proteins such as occludin or claudin(s), hypoxia-induced enhancement of barrier function occurs through diverse pathways, ranging from increased mucin production [21] and molecules that modify mucins (e.g., intestinal trefoil factor) [17], to xenobiotic clearance (P-glycoprotein) [18] to nucleotide metabolism (ecto-5′-nucleotidase, CD73) [19][20] and nucleotide signaling (adenosine A2B receptor) [20] (Fig. 2).…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 99%
“…Although the presence of ectonucleotidases is critical for maintaining the vascular homeostasis, little is known about its expression regulation at the molecular level. Modulated expression of NTPDase1 and ecto-5′-NT/CD73 has been closely associated with inflammatory cytokines, oxidative stress, and hypoxia [46][47][48][49]. Therefore, the pro-inflammatory environment present in C6NT2 glioma-implanted rats may modulate the ectonucleotidase expression in platelets.…”
Section: Discussionmentioning
confidence: 99%